The risk-taking channel of monetary policy in the US: Evidence from corporate loan data - Manthos D. Delis; Iftekhar Hasan; Nikolaos Mylonidis (Bank of Finland, 2017)
To study the presence of a risk-taking channel in the US, we build a comprehensive dataset from the syndicated corporate loan market and measure monetary policy using different measures, most notably Taylor (1993) and Romer and Romer (2004) residuals. We identify a negative relation between monetary policy rates and bank risk-taking, especially in the run up to the 2007 financial crisis. However, this effect is purely supply-side driven only when using Taylor residuals and an ex ante measure of bank risk-taking. Our results highlight the sensitivity of the potency of the risk-taking channel to the measures of monetary policy innovations.
URN:NBN:fi:bof-201708091482
Keywords: G21; G01; E43; E52; 330